Influence of plasma background including neutrals on scrape-off layer filaments using 3D simulations. (August 2017) - Schwörer, D.; Walkden, N.R.; Leggate, H.; Dudson, B.D.; Militello, F.; Downes, T.; Turner, M.M.
Highlights: 3D full-fluid filament simulations including neutrals carried out in BOUT++. No significant influence of neutrals on filament observed. Increasing background density reduces radial velocity of the filaments. Abstract: This paper investigates the effect of the plasma background, including neutrals in a self-consistent way, on filaments in the scrape-off layer (SOL) of fusion devices. A strong dependency of filament motion on background density and temperature is observed. The radial filament motion shows an increase in velocity with decreasing background density and increasing background temperature. In the simulations presented here, three neutral-filament interaction models have been compared, one with a static neutral background, one with no interaction between filaments and neutrals, and one co-evolving the neutrals self consistently with the filaments. With the background conditions employed here, which do not show detachment, there are no significant effects of neutrals on filaments, as by the time the filament reaches maximum velocity, the neutral density has not changed significantly.